1860 Md. Code 903 - (:unkn) unknown (My University, 1860)
§ 128: They may impose a fine of one dollar on any person who may discharge a gun or other firearms in the said town on any day except on days when the militia may be mustered or paraded therein, and the like fine upon all persons who may suffer their chimneys or any of them to flame out; or upon any person driving, training or riding any horse at an immoderate gait through the streets.
Keywords: DISCHARGE